An unusual case of Essential Thrombocythemia in coexistence with Breast cancer (Bangladesh Journal of Medical Science, 2022)
Essential thrombocythemia (ET) is an extremely rare myeloproliferative neoplasm (MPN) which is characterized by persistent, non-reactive thrombocytosis (> 450 X 109/L) and an increased risk for thrombotic events.These patients have an increased risk of both hematological and non-hematological malignancies however the risk of breast cancer in MPN is not increased in comparison to general population. We hereby present an extremely unusual case of ET in a 38 years old female (diagnosed with breast cancer), which came to light on routine pre-surgical work up of the patient.Diagnosis was confirmed on bone marrow aspiration clubbed with JAK 2 mutation. Patients with ET have an increased risk of thrombosis thereby it becomes challenging for the clinician to operate on a coexistent solid tumor. On extensive literary search, there was a single case of coexistent Breast Cancer and Essential Thrombocythemia and we are reporting second such coexistence to the best of our knowledge.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 463-466